Effects of Sleep Restriction on Self-Reported Putting Performance in Golf. Issue 3 (June 2022) - Nishida, Masaki; Chiba, Taishi; Murata, Yusuke; Shioda, Kohei
In the present study, we aimed to explore the effects of sleep restriction (SR) on self-reported golf putting skills. Eleven collegiate golfers participated in a self-reported, counterbalanced experimental study under two conditions: (a) a SR condition in which sleep on the night prior to putting was restricted to 4–5 hours, and (b) a habitual normal sleep (NS) condition on the night before the putting test. Following each sleep condition, participants engaged in ten consecutive putting tests at 7 am, 11 am, and 3 pm. Participants reported their subjective sleepiness before each time frame, and their chronotype, defined as their individual circadian preference, was scored based on a morningness–eveningness questionnaire (MEQ). Participants restricted sleep to an average period of 267.6 minutes/night ( SD = 51.2 ) in the SR condition and 426.2 ( SD =38.0) minutes/night in the NS condition. A two-way analysis of variance revealed a significant main effect of the sleep condition on the lateral displacement of putts from the target (lateral misalignment) ( p = 0.002). In addition, there was a significant main effect of time on distance from the target (distance misalignment) ( p = 0.017), indicating less accuracy of putting in the SR condition. In the SR condition, the MEQ score was positively correlated with distance misalignment at 3 pm ( ρ = 0.650, p = 0.030), suggesting that morningness types are susceptible to the effects of SR on putting performance. Our findings suggest that golfers should obtain sufficient sleep to optimize putting performance.